(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Startup India is a flagship initiative of the Government of India, intended to build a strong eco-system for nurturing innovation and Startups in the country. Under this initiative a Startup India Portal has been set up which shall serve as a platform for facilitation of Startup recognition, access to information related to incubators, mentors, Angel Funds, Venture Funds etc. Startup India campaign is based on an action plan aimed at promoting bank financing for start-up ventures to boost entrepreneurship and encourage startups with jobs creation. The campaign was first announced by Prime Minister Narendra Modi in his 15 August 2015 address from the Red Fort. It is focused on to restrict role of States in policy domain and to get rid of license raj and hindrances like in land permissions, foreign investment proposal, environmental clearances. It was organized by Department of Industrial Policy and Promotion (DIPP). So the present study is conducted to provide overview of startup in India. It will give ideas to the society and the potential entrepreneurs about various schemes and assistance under the Startup India scheme. Further, it will provide a basis for future research in the concerned field.